If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -9x = 35 + -16x Solving 12 + -9x = 35 + -16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16x' to each side of the equation. 12 + -9x + 16x = 35 + -16x + 16x Combine like terms: -9x + 16x = 7x 12 + 7x = 35 + -16x + 16x Combine like terms: -16x + 16x = 0 12 + 7x = 35 + 0 12 + 7x = 35 Add '-12' to each side of the equation. 12 + -12 + 7x = 35 + -12 Combine like terms: 12 + -12 = 0 0 + 7x = 35 + -12 7x = 35 + -12 Combine like terms: 35 + -12 = 23 7x = 23 Divide each side by '7'. x = 3.285714286 Simplifying x = 3.285714286
| x^3-9x^2+24x+1=0 | | 4+3*5=x | | 4x-x-2=34 | | 3bc=12+9bc | | s+808=57 | | -(7-4x)=7 | | 114=2u | | f29=7 | | 11x+11=4x+158 | | 42+5x=9-8x | | v+66=993 | | 6*8=0 | | 284-7x=38x+24 | | 7x+2x-3=5x+9 | | q+407=73 | | -19x-21=35-x | | xy=29 | | 20x^2+60x+45=0 | | q+ -407= -73 | | 3x+1=6x-2 | | r+450=996 | | 4-x=15 | | d-732=-485 | | 630-7x=3x | | 3x+69=8x+12 | | 2+(x-7)+1=7 | | -28-7=10x+23 | | x^6=1.4 | | 2+(x-3)+1=7 | | 35=7d | | 11-t=21 | | 40x^2+20x=0 |